Movement characteristics and heart rate profiles displayed by female university ice hockey players - Jackson, J.; Snydmiller, G.; Game, A.; Gervais, P.; Bell, G. (International Journal of Kinesiology & Sports Science, 2016)
Background: Women`s ice hockey is widely popular but the various movement patterns, heart rate responses and work to rest ratios during competitive games has not been adequately investigated. Objectives: This study determined the frequency and duration of movements that female players perform in ice hockey games using time-motion analysis. The intensity of the game activities were also assessed by heart rate (HR) responses and work to rest ratios (W:R). Methods: Twenty-two university female ice hockey players were filmed performing a number of movements during three regular season league games. Results: The following movement patterns were categorized in percent of time performed during the games: forward gliding on ice (36.3 ± 6.2%), forward skating at a moderate intensity (31.2 ± 6.2%), backward glide (9.5 ± 4.1%), standing (7.1 ± 5.9%), struggling (6.3 ± 2.6%), forward skating at maximal intensity (5.3 ± 3.3%), backwards skating at moderate intensity (3.1 ± 3.3%). Defense stood and glided backward more than forwards but skated less at a high or maximal intensity. Positional differences were also observed during different game play situations. The highest HR achieved during shifts was 182 ± 10 and HR averaged 174 ± 9 bpm for the whole duration of the shifts. The shift and game W:R ratios for all players were 1:1.6 and 1: 3.7, respectively. Conclusions: The findings of this study indicate that female ice hockey games are played at a low to moderate intensity most of the time (~84% of the time spent) and are interspersed with brief, intermittent high intensity activities that vary according to player position and game play situation. It was also apparent that female players display markedly high HR responses during game-play indicative of a substantial cardiovascular demand in ice hockey.